Therapeutic implications of toll-like receptors in peripheral neuropathic pain. (January 2017) - Thakur, Krishan K.; Saini, Jyoti; Mahajan, Kanika; Singh, Dhyanendra; -->Jayswal, Dinkar P.; Mishra, Srishti; -->Bishayee, Anupam; Sethi, Gautam; Kunnumakkara, Ajaikumar B.
Graphical abstract: Abstract: Neuropathic pain is a state of chronic pain arising after peripheral or central nerve injury. These injuries can be mediated through the activation of various cells (astrocytes, microglia and Schwann cells), as well as the dissolution of distal axons. Recent studies have suggested that after nerve injury, Toll-like receptors (TLRs) involved in Wallerian degeneration and generation of neuropathic pain. Furthermore, these TLRs are responsible for the stimulation of astrocytes and microglia that can cause induction of the proinflammatory mediators and cytokines in the spinal cord, thereby leading to the generation and maintenance of neuropathic pain. Indeed considering the prevalence of neuropathic pain and suffering of the affected patients, insights into the diverse mechanism(s) of activation of TLR signaling cascades may open novel avenues for the management of this chronic condition. Moreover, existing therapies like antidepressants, anticonvulsants, opiates and other analgesic are not sufficiently effective in reducing the pain. In this review, we present substantial evidences highlighting the diverse roles of TLRs and their signaling pathways involved in the progression of neuropathic pain. Furthermore, an elaborate discussion on various existing treatment regimens and future targets involving TLRs has also been included.